Teacher-Child Relationships from Kindergarten to Sixth Grade: Early childhood predictors of teacher-perceived conflict and closeness - Jerome, Elisabeth M. (2008)
This article examines general trends in teacher-reported conflict and closeness among 878 children from kindergarten through sixth grade, and examines early childhood characteristics that predict differences in initial levels and growth of conflict and closeness over time. Results indicated modest stability of teacher-perceived conflict and closeness through sixth grade, with relatively greater stability in perceptions of conflict. Levels of conflict at kindergarten were higher for children who were male, Black, had greater mean hours of childcare, had lower academic achievement scores, and had greater externalizing behavior. Children identified as Black and those with less sensitive mothers were at greater risk for increased conflict with teachers over time. Levels of teacher-reported closeness were lower when children were male, had lower quality home environments, and had lower academic achievement scores. The gap in closeness ratings between males and females increased in the middle-elementary school years. Additional analyses were conduced to explore differences in teacher-ratings of conflict between Black and White students.